The Role of Work Engagement and Customer Service Orientation in Driving Employee Performance - Tria Handayani; Faqih Nabhan (Universitas Diponegoro, 2025)
This study aims to examine Perceived Organizational Support (POS) in improving employee performance, which is strengthened by work engagement and customer service orientation. The sample used was 92 respondents from microfinance institutions in Salatiga, using a purposive sampling technique, and then distributing questionnaires directly. Data processing with SmartPLS 4.0 software. This research concludes several findings, first, POS is proven to encourage increased employee performance, strengthen work engagement, and increase customer service orientation. Second, work engagement and customer service orientation have a strong influence on improving employee performance. Third, work engagement and customer service orientation that are well managed are proven to be able to mediate the success of POS in improving employee performance. This research further clarifies the Social Exchange Theory (SET) perspective and provides further evidence regarding the role of POS in encouraging increased employee performance.